Complementation of adenovirus type 5 host range mutants by adenovirus type 12 in coinfected HeLa and BHK-21 cells. - Rowe, D T (1981)
We have studied the ability of adenovirus type 12 (Ad12) to complement the Ad5 transformation-defective host rang (hr) mutants during infection of human cells (HeLa) or hamster cells (BHK-21). The group I mutant hr3 (mapped within 1.3 to 3.7 map units), which is incapable of synthesizing viral DNA, was complemented for both DNA synthesis and infectious virus production in nonpermissive HeLa cells during coinfection with Ad12. Similarly, the group II mutant hr6 (6.1 to 9.4 map units), which does synthesize DNA, was also shown to be complemented for virus production. When the host cells were BHK-21, an established hamster cell line that is permissive for Ad5 but nonpermissive for Ad12 DNA synthesis and virus production, coinfection with Ad5 and Ad12 did not overcome the block to Ad12 DNA synthesis. Coinfection of BHK-21 cells with Ad12 and either hr3 or hr6 leads to the complementation of only the group I mutant (hr3). The inability of Ad12 to complement hr6 in BHK-21 cells may be due to the failure of Ad12 to express an early gene product from the region corresponding to early region 1B (4.5 to 11 map units) Ad5 where hr6 and the other group II mutations are located.